ANALISIS PERTUMBUHAN PLANLET RUMPUT LAUT (Gracilaria Verrucosa) DI BALAI PERIKANAN BUDIDAYA AIR PAYAU (BPBAP) TAKALAR, SULAWESI SELATAN - Marliani Loainak, Maria; Iyen, Hartina; D.B.R Minggo, Yohanes (Universitas Cokroaminoto Palopo, 2025)
This research aims to determine the growth of Gracilaria verrucosa seaweed plantlets and to determine the environmental parameters that support the growth of Gracilaria verrucosa seaweed in the BPBAP Takalar seaweed tissue culture laboratory. This research took place in seaweed tissue culture, Takalar Brackish Water Aquaculture Fisheries Center (BPBAP), Mappakalompo Village, South Galesong District, Takalar Regency, South Sulawesi Province. This research was carried out for four months, namely from August to December 2024. The research method used analysis of variance to see the comparison of growth rates. The parameters observed during the research were observations of absolute growth, specific growth rate and ADG (Avarage Daily Growth). Based on the results obtained in this research, it can be concluded that container 1 has a higher average growth rate compared to container 2 and container 3. The respective average growth rates for container 1, container 2, and container 3 are 0.511%, 0.274%, 0.407%. Environmental parameters that support the growth of Gracilaria verrucosa seaweed plantlets include temperature, light intensity, salinity and fertilizer.